TGF-b signaling in cartilage homeostasis and osteoarthritis. - Finnson, K; Chi, Y; Bou-Gharios, G; Leask, A; Philip, A (2012)
Healthy cartilage is maintained by a delicate balance between the anabolic and catabolic activities of articular chondrocytes. This involves actions of numerous cytokines and growth factors that regulate the synthesis and degradation of extracellular matrix components which maintain the functional integrity of the joint. An imbalance between the activities of these anabolic and catabolic factors leads to cartilage degradation resulting in osteoarthritis (OA), a chronic degenerative joint disorder characterized by destruction of articular cartilage, alterations of subchondral bone and synovial fibrosis. Among the cytokines and growth factors that have been studied in the context of cartilage homeostasis and OA, transforming growth factor-beta TGF-beta has emerged as an important molecule that plays a critical role in the development, growth, maintenance and repair of articular cartilage. Deregulation of its signaling and responses has been shown to be involved in OA. Several components of the TGF-beta pathway, including extracellular, cell surface and intracellular molecules, display altered expression or action in OA. In this review, we discuss the regulatory mechanisms of TGF-beta signaling and link these mechanisms to cartilage function, highlighting the important role of TGF-beta in maintaining cartilage function and integrity. We also summarize the alterations in the molecular events of TGF-beta signaling and responses that may contribute to OA progression and discuss the potential of targeting the TGF-beta signaling pathway for the development of novel therapies for OA.